OVERLAPPING BETWEEN THE HUNTING SEASONS OF THE MAIN GAME SPECIES AND THE PICKING INTERVALS OF TRUFFLES IN ROMANIA - Cristian Mihai ENESCU; Marian DRĂGOI (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The main objectives of this study to test the chain feeder system before and after modifying under three levels of chain feeder speeds was 25,30 and 35m/min and three levels of opening gate feed area was18,27and 36 cm2.this modification using bearing with corner wheel lead tominimize energy and wearing between corner wheel feeder chine to increase the efficiency of chain feeder with subtle amount of forage components on trough chicken nurture. The results showing increased the Feeding rate of feeder from 31 to 81 kg/min when opening feed area increased from 18 to 36 cm2 at 25 m/ min chain speed , at the same conditions, the total amount of feed increased the Feeding rate of feeder from 620 to 1,620 g/m Also the Feeder efficiency increased from 36.90 to 96.40% when using the opening feed area increased from 18 to 36 cm2 at 25 m/ min chain speed The feeding system performance was evaluated under with and without load, the power requirement with ordinary fillers before modified deceased from 1.089 to 0.941 kW withload and without load at 25 m/ min chain speed also deceased from 1.026 to 0.846 kW withload and without load at modified system. The feeder chine loses increased from 280 to 900 g. when opening feed area increased from 18 to 36 cm2 .Also Wearing behaviour compared between wheel before and after using bearing the wearing rate decreased from 0.90 to 0.35g/h before and after modified.